Pemahaman konsep matematika siswa kelas IV sekolah dasar materi luas dan keliling bangun datar berbantu media youtube - Rifdah, Salsabila Nur; Kurniawan, Sandra Bayu; Budiharto, Tri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the results of the analysis of students' understanding of mathematical concepts, and the indicators that are mastered and not yet mastered by students in terms of area and circumference of flat shapes for YouTube video media during the limited PTM period. The research method used is descriptive qualitative method with case study. The subjects in this study were students of class IVA at SDN Panularan No. 6 Surakarta in the academic year 2021/2022. The number of students as many as 28 people. Data collection techniques used are observation, interviews, tests, and documentation. The data analysis technique used is analysis according to Miles and Huberman through 3 stages, including data reduction, data presentation, data verification/conclusion. The results showed that students' understanding of mathematical concepts on the area and perimeter of flat shapes using youtube video media in class IVA SDN Panularan No.06 Surakarta was generally in the medium category. In this study, 5 indicators of mathematical concept understanding were used, 3 indicators were categorized as medium, and 2 indicators were categorized as low. Indicators included in the moderate category include: restating the concepts learned, presenting concepts in mathematical form, developing the requirements of a concept by choosing procedures to be used in solving problems, while the 2 indicators are classifying objects according to certain properties based on mathematical concepts , and applying the concept in a problem is still low.